Liquid chromatography-tandem mass spectrometric method for trace quantification of ethyl methanesulfonate: a genotoxic impurity in dapoxetine hydrochloride - Ravi Kiran Panchakarla; Punna Rao Ravi; Venkata Gowri Chandra Sekhar Kondapalli (SpringerOpen, 2021)
Abstract Background Dapoxetine hydrochloride is a selective serotonin reuptake inhibitor drug for treating premature ejaculation. This study was designed to develop and validate a sensitive and selective LC-MS/MS method for trace analysis of genotoxic impurity ethyl methanesulfonate in Dapoxetine hydrochloride. Results Chromatographic separation was achieved on the Shodex RSpak DS-413 column, 150 × 4.6 mm, 3.0 µm using eluent containing a equal volumes of acetonitrile and 0.1% v/v formic acid in water was used in the isocratic elution mode at a pump flow of 1.0 mL/min. No interference was observed at the retention time of ethyl methanesulfonate, indicating that the developed method is specific and selective for trace level quantification.The developed method was found to be linear in the concentration range of 1-50 ppm with coefficient of regression of 0.9997. Detection limit and quantification limit were determined to be 0.6 ppm and 1.0 ppm respectively. Acceptable RSD values (< 10.0%) and recovery results (> 90%) obtained from the accuracy and precison experiments indicate that the developed method is precise and accurate in the concentration range of 1-50 ppm. Ethyl methanesulfonate solutions were stable for two days when stored at room and refrigerated temperatures. Conclusion The developed method has the ability to quantify ethyl methanesulfonate in dapoxetine hydrochloride. Thus, the anticipated method has high probability to adopt in the quality testing laboratories of pharmaceutical industry.